Penerapan Aplikasi Si Mas Latif (Atasi Kecemasan Dengan Relaksasi Dan Terapi Kognitif), Sebagai Upaya Mengurangi Masalah Psikososial - Indra Ruswadi; Nafisah Itsna Hasni; Kayubi Kayubi (ASPIRASI : Publikasi Hasil Pengabdian dan Kegiatan Masyarakat, 2023)
Anxiety is a normal emotion that everyone has. Anxiety appears as a brain response to stress that warns of potential danger. Problems arise if the anxiety occurs continuously and even interferes with life. Anxiety like this can have a bad impact on body health and this is what is called an anxiety disorder. To reduce this anxiety problem, deep breathing relaxation and cognitive therapy can be done. The aim of community service is to find out about the application of the Si Mas Latif application (Overcoming Anxiety with Relaxation and Cognitive Therapy), in people who experience psychosocial anxiety problems at the Kertasemaya Health Center, Indramayu Regency.The method used is to create an application that can be used as a guide in overcoming anxiety using deep breathing therapy and cognitive behavioral therapy and outreach to program holders and the community using health services.Result: availability of the Si Mas Latif application (Overcoming Anxiety with Relaxation and Cognitive Therapy) and this application has been in HKI and socialization has been carried out to the Kertasemaya Community Health Center program holders.